If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(6x+1)+(9x-23)=180
We move all terms to the left:
(6x+1)+(9x-23)-(180)=0
We get rid of parentheses
6x+9x+1-23-180=0
We add all the numbers together, and all the variables
15x-202=0
We move all terms containing x to the left, all other terms to the right
15x=202
x=202/15
x=13+7/15
| -6+6(1-8m)=-288 | | n/25+979=998 | | 0.6(x+6)=11 | | 4(2+y)-3y=1 | | 847-h=327 | | 7=s/6-1 | | -8(4v+2)=176 | | 2w^2+6w-520=0 | | m/10+49=57 | | x^2+√5x-19=0 | | 1,2(3x+6)=-4 | | 6(4x+5)=40x+14 | | 1+4(2x-1)=6.25x+26 | | 30-5kk=-2 | | 6d-30=42 | | 8=56/w | | 66+y-8+y+6=180 | | 96-j=44 | | 4(y-3)=5y+51 | | 12(2x32-3)=6(32) | | (3x)+(5x-64)=180 | | 1=m+6/20 | | 62+61+19v=180 | | 30+3u=96 | | 2w^2+10w-651=0 | | 44+6s+2s=180 | | 4x+6−7x+9=18 | | 7x+4×=-66 | | 3n+1n=-6 | | 106+44+2z=180 | | 2w^2+32w-6144=0 | | 29-q=10 |